2021
DOI: 10.1111/ppe.12757
|View full text |Cite
|
Sign up to set email alerts
|

The maternal health study: Study design update for a prospective cohort of first‐time mothers and their firstborn children from birth to age ten

Abstract: Background Maternal health is critical to the health and well‐being of children and families, but is rarely the primary focus of pregnancy and birth cohort studies. Globally, poor maternal health and the exposure of women and children to family violence contribute to the perpetuation and persistence of intergenerational health inequalities. Objectives The Maternal Health Study was designed to investigate the contribution of social and obstetric risk factors to common maternal physical and psychological morbidi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 94 publications
0
13
0
Order By: Relevance
“…Follow-up data were collected from mothers at 3, 6, and 12 months, 4- and 10 years postpartum, and from children at 10 years. Further details are presented in the study protocol (Brown et al, 2006) and update (Brown et al, 2021). Ethical approval for the study was granted by the ethics committee of the participating hospitals, as well as the Human Research Ethics Committee of La Trobe University (2002/38) and the Royal Children’s Hospital (27056A, 33127A, 34058A, and 36189A).…”
Section: Methodsmentioning
confidence: 99%
“…Follow-up data were collected from mothers at 3, 6, and 12 months, 4- and 10 years postpartum, and from children at 10 years. Further details are presented in the study protocol (Brown et al, 2006) and update (Brown et al, 2021). Ethical approval for the study was granted by the ethics committee of the participating hospitals, as well as the Human Research Ethics Committee of La Trobe University (2002/38) and the Royal Children’s Hospital (27056A, 33127A, 34058A, and 36189A).…”
Section: Methodsmentioning
confidence: 99%
“…It is not possible to calculate a precise response fraction as many women received invitations via more than one pathway. Comparison of participant characteristics with those of all nulliparous women giving birth at Victorian public hospitals during the study period showed that the sample was representative in relation to method of birth, infant birthweight and gestation, but that younger women (18–24 years of age, 14.1% versus 29.8%) and women born overseas of non-English speaking background (16.2% versus 21.5%) were under-represented [ 33 , 34 ]. At enrolment (mean of 15 weeks’ gestation), a majority of women were living with a partner and had completed some post-secondary education (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…certificate, diploma or university degree). Further information about sample characteristics is available in a recent study update [ 34 ]. Women who participated in 10-year follow-up (63.2% of the original cohort) were more likely to be older, Australian born, tertiary educated, not in receipt of a government health care card, and less likely to have reported IPV or depressive symptoms in the year following the birth of their first child ( S1 Table ).…”
Section: Resultsmentioning
confidence: 99%
“…IPV refers to a “constellation of abuse” which includes controlling and intimidating behaviors, and such emotional abuse tactics can also have detrimental effects for women and children's health, making it important to include emotional abuse in conceptualizations of IPV (Dobash & Dobash, 2004). Additionally, few studies have been conducted with community samples, and very few have included repeated measurement of IPV at multiple timepoints across childhood (Brown et al, 2021).…”
Section: Ipv and Child Developmentmentioning
confidence: 99%